Pengaturan Mogok Kerja Tidak Sah Berdasarkan Keputusan Menteri Tenaga Kerja dan Transmigrasi Nomor KEP.232/MEN/2003: Studi Kasus Putusan Nomor 361/Pdt.Sus-PHI/2023/PN.Jkt.Pst - Firdaus, Heldy; Parhusip, Sahat M; Harahap, Iqbal Fadillah; Muchlis, Rizaldy; Ramdhan, Abdullahsyah Mahdi (Journal of Industrial Relations Studies, 2025)
This journal examines the legal aspects of unlawful strikes, focusing on the case of Sunarto, a permanent employee and Chairman of the PB-FGSBM Workers' Union at PT Sinar Terang Kencana, who was terminated following a strike deemed unlawful under Indonesian labor law. The study analyzes the compliance of the strike with the provisions of Ministerial Decision No. KEP.232/MEN/2003, particularly Article 3(a), which outlines the procedural requirements for a lawful strike. The research employs a normative juridical method with a case study approach, evaluating the validity of the strike and the legal protection for union leaders. The findings highlight that the strike failed to meet the formal requirements due to inadequate bipartite negotiations, leading to the court's ruling in favor of the termination's legality. This study underscores the importance of procedural clarity in industrial actions and the need for stronger legal protections for workers to ensure fairness in industrial relations